Determinants of online consumer behavior in Indian context An empirical study - Raj, Prem Sherin (Digital Repository of Theses - SSBM Geneva, 2024)
Consumer behavior is a complex phenomenon and online consumer behavior is far more complex as it’s nonlinear and dynamic in nature. Consumers are moving rapidly from brick-and-mortar shops to e-commerce portals and hence it’s imperative to understand their shopping behavior and accordingly ensure stickiness and repeated visits. The competitive landscape of e-shopping is vast and each brand in the space is trying to do segmenting, targeting, and positioning in their own understanding and consumer insights, moreover with technology catching up with ease and convenience the market size will grow exponentially and hence the study on this subject must be continuous to understand the ever-evolving consumer behavior. Consumer attraction and retention is the major attribute for any business and online consumer behavior will be different in different context and geography. To decode this online consumer behavior the extended theory of online consumer behavior was studied in Indian context with most of the important variable’s inclusion. This model was tested for descriptive, inferential and PLS- SEM for model fitness.